استخدام القواميس المطبوعة والرقمية كاستراتيجية لتحسين مهارات الترجمة: تحليل مقارن وتأملي - Nurul Aini; Erlina; Yeni Lailatul Wahidah; M. Riza Pahlefi (Arabiyyatī: Journal of Arabic Language Education, 2025)
Translation skills are important in learning Arabic. Dictionaries are the primary reference tools in the translation process, and technological developments have shifted the dominance of printed dictionaries to digital dictionaries. This change raises questions about the effectiveness of both in improving translation skills. This study aims to analyze the patterns of use of printed and digital dictionaries, their similarities and differences in practical usage, and the optimal strategies for their use in supporting translation skills, particularly for students of Arabic Language Education at UIN Raden Intan Lampung. This study uses a descriptive qualitative approach with a case study research design. Data were collected through retrospective observation, interviews, documentation, and reflective post-translation tests to reinforce the findings. The analysis was conducted comparatively by mapping the contributions of both types of dictionaries to the accuracy of meaning, sentence structure, and vocabulary accuracy. The results showed that printed dictionaries helped deepen understanding of vocabulary and context, but were less efficient in terms of time use. Conversely, digital dictionaries offered speed and ease of access, although they often led students to take meanings instantly without in-depth analysis. The post-test findings show that students who combine the use of both dictionaries obtain better translation results than those who only rely on digital dictionaries. This study concludes that a combined usage strategystrategy is the most effective option for improving students' translation skills.